(untitled) (Revista Brasileira de Agroecologia, 2010)
The ecological rationality of natural resourse management of traditional farmers, has led to agroecosystems sustainability. Understanding ecological rationality of farmers that do not follow a traditional agriculture, would contribte to improve sustainable agriculture. However it is difficult becauseof the complexity of the term “ecological rationality” and the lack of a methodology to study it. In this contex, a methodology to deal with ecological rationality, is proposed and validated in three horticulturalists groups in La Plata, Argentine. The suggested method has eight steps: 1) framework definition, 2) hipothesis, 3) dimension of analisys definition, 4) field definition, 5) indicators built , 6) data survey, 7) results analisys, 8) hipothesis validation. The applied methodology allowed to develop a sensible and pertinent indicator group to analize the ecological rationality. It was observed that organic and small farmers with less oportunities to incorporate external inputs, develop an ecological rationality more suitable for natural resourses conservation than capitalize ones.